AN EMPIRICAL ANALYSIS OF STOCK MISPRICING: EVIDENCE FROM UK STOCK MARKET - Wang, Lujia (2012)
In this dissertation, mispricing in the UK stock market is investigated. It is well documented that stock mispricing has been discovered in stock markets in the world. This paper first reviews the mispricing evidences, the models valuing stocks, and hypotheses explaining mispricing established by previous researchers. Then, a sample test is conducted to analyse the stock mispricing in UK stock market. A large panel of UK firms listed on London Stock Exchange has been used to accomplish the empirical examination. According to results of portfolio classification analysis and regressions, it is found that 1) firm characteristics measured by book-to-market ratio and firm size have a significantly negative/positive impact on mispricing of stock; 2) there‘s significantly positive relationship between the stock mispricing and the inflation; 3) stocks with high mispricing underperform stocks with low mispricing; 4) arbitrage opportunities and stock mispricing are positively related.